Macroscopic detection of demyelinated lesions in mouse PNS with neutral red dye - Reiji Yamazaki (Nature Portfolio, 2021)
Abstract Lysophosphatidylcholine (LPC)-induced demyelination is a versatile animal model that is frequently used to identify and examine molecular pathways of demyelination and remyelination in the central (CNS) and peripheral nervous system (PNS). However, identification of focally demyelinated lesion had been difficult and usually required tissue fixation, sectioning and histological analysis. Recently, a method for labeling and identification of demyelinated lesions in the CNS by intraperitoneal injection of neutral red (NR) dye was developed. However, it remained unknown whether NR can be used to label demyelinated lesions in PNS. In this study, we generated LPC-induced demyelination in sciatic nerve of mice, and demonstrated that the demyelinated lesions at the site of LPC injection were readily detectable at 7 days postlesion (dpl) by macroscopic observation of NR labeling. Moreover, NR staining gradually decreased from 7 to 21 dpl over the course of remyelination. Electron microscopy analysis of NR-labeled sciatic nerves at 7 dpl confirmed demyelination and myelin debris in lesions. Furthermore, fluorescence microscopy showed NR co-labeling with activated macrophages and Schwann cells in the PNS lesions. Together, NR labeling is a straightforward method that allows the macroscopic detection of demyelinated lesions in sciatic nerves after LPC injection.